2014 International Conference on Electrical Machines (ICEM) 2014
DOI: 10.1109/icelmach.2014.6960566
|View full text |Cite
|
Sign up to set email alerts
|

Analytical model of a permanent magnet brushless DC motor with non-linear ferromagnetic material

Abstract: This paper presents an analytical model for determining air-gap radial and tangential magnetic field in permanent magnet brushless dc (PMBLDC) motor. The solution is based on two-dimensional analysis in polar coordinates for radially magnetized magnet. Effects caused due to non-linear behavior of the stator ferromagnetic yoke are mainly considered. Radial and tangential magnetic field, back emf and cogging torque are calculated and are validated with finite element results. The finite element analysis demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…These papers have considered stator and rotor yoke to be infinitely permeable or have assumed that the motor operates in linear region of B − H curve [10]- [29]. Very few researchers have included the effect of non-linear behavior of ferromagnetic material [10], [30]- [32]. Some researchers [10], [30] have included the saturation effect by introducing a saturation factor to modify the air-gap length.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These papers have considered stator and rotor yoke to be infinitely permeable or have assumed that the motor operates in linear region of B − H curve [10]- [29]. Very few researchers have included the effect of non-linear behavior of ferromagnetic material [10], [30]- [32]. Some researchers [10], [30] have included the saturation effect by introducing a saturation factor to modify the air-gap length.…”
Section: Introductionmentioning
confidence: 99%
“…However, in this work, the approximated magnetization curve is able to represent only a section of the B − H curve. In [32], authors have presented an iterative technique to include the non-linear properties of core material but have limited the analysis only to no-load operation of the motor. From this discussion, it is observed that the effects of ferromagnetic material property have not been thoroughly investigated in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the armature slotting is taken into account through the SC mapping method. The analytical magnetic field distribution is determined in five or six homogeneous layers (i.e., exterior, slotless stator, winding/air-gap, magnets, and rotor) [29][30][31]. In [29], the magnetic permeabilities in stator/rotor iron cores have a constant value corresponding to linear zone of the B(H) curve.…”
Section: State-of-the-art: Saturation In Maxwell-fourier Methodsmentioning
confidence: 99%
“…In [29], the magnetic permeabilities in stator/rotor iron cores have a constant value corresponding to linear zone of the B(H) curve. An iterative technique to include the nonlinear properties of core material has been developed in [30] (for a no-load operation) and [31] (for a load operation whose the source term in the slot caused by the armature currents is represented by a winding current region over the stator slot-isthmus). In this type of modeling, the local distribution of flux densities in the teeth and slots is neglected.…”
Section: State-of-the-art: Saturation In Maxwell-fourier Methodsmentioning
confidence: 99%
“…In literature, there are many papers that are related to the design, modeling or control of the BLDC motors, considering the time-stepping FE approach (Jang et al, 2002;Lin et al, 2004;Kim et al, 2004). However, the problems are always nonlinear because of the presence of ferromagnetic materials (Lin et al, 2004;Dalal and Kumar, 2014). Moreover, the existence of permanent magnets has an impact on produced magnetic torque, which, in general, is a Nonlinear finite element model 633 nonlinear function of the winding currents and also depends on rotor position (Park et al, 2000, Ko et al, 1993.…”
Section: Introductionmentioning
confidence: 99%